The Use of English Outside the Classroom by Students of the English Education Study Program - Libertina Lase (General English Education, 2024)
English is a widely used language in various countries. The purpose of this study is to determine whether students use English beyond the classroom and to identify reasons for not doing so, with a focus on speaking. The study utilizes a quantitative research method, involving descriptive statistical data analysis, with students from the English 2023 program as subjects. Data was collected through a Likert scale with 10 statements and reasons for not using English outside the classroom. Results indicate that 71 students used English outside of class, with lack of participation being the primary reason for those who did not. It is important for students to use English beyond the classroom to improve their speaking skills and vocabulary.